2021
DOI: 10.1080/02642069.2021.1873296
|View full text |Cite
|
Sign up to set email alerts
|

Masked smiles matter – employee verbal expertise and emotion display during COVID-19

Abstract: Throughout the customer journey, the employee-customer interaction drives customer responses. The COVID-19 pandemic has dramatically influenced shopping behavior with face masks playing a major role. This research investigates how consumer behavior has changed and how frontline employee (FLE) nonverbal (emotional facial expressions) and verbal cues (verbal expertise) influence customer responses dependent on whether FLEs wear a face mask or not. Semi-structured interviews among consumers, an open association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 68 publications
1
12
1
Order By: Relevance
“…The results uncovered a chain of effects by which seeing a salesperson wearing a face mask heightened consumer perceptions of salespeople credibility, which in turn positively influenced consumer satisfaction with the service. Therefore, in line with other studies (e.g., Hofmann et al , 2021), we conclude that face masks are generally not a barrier to interacting with salespeople; instead, they add trustworthiness and reassure most customers. To further confirm these positive effects and verify whether face masks’ impact on service satisfaction further extends to consumer behavioral intentions (i.e., word-of-mouth intention), we ran a third study to examine the effect of not using face masks in service encounters.…”
Section: Empirical Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…The results uncovered a chain of effects by which seeing a salesperson wearing a face mask heightened consumer perceptions of salespeople credibility, which in turn positively influenced consumer satisfaction with the service. Therefore, in line with other studies (e.g., Hofmann et al , 2021), we conclude that face masks are generally not a barrier to interacting with salespeople; instead, they add trustworthiness and reassure most customers. To further confirm these positive effects and verify whether face masks’ impact on service satisfaction further extends to consumer behavioral intentions (i.e., word-of-mouth intention), we ran a third study to examine the effect of not using face masks in service encounters.…”
Section: Empirical Studiessupporting
confidence: 92%
“…Investigating the effects of face masks in dyadic service interactions, Hofmann et al (2021) showed that, despite some potential discomforts (i.e., difficulties in communication), face masks lower the perceived infection risk, so individuals generally hold a positive attitude toward the obligation to wear them. Therefore, failing to comply with the new social norm of wearing a mask could also cause a service failure, which may ultimately impact consumer intentions (e.g., spreading positive word of mouth for a service).…”
Section: Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of facemasks has been shown in prior research as conducive to successful service interactions during the COVID-19 crisis (e.g. Hofmann et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%